Inventory of Macroscopic Fungi in Protected Forest Areas Malaka District Chartery - Lukas Pardosi; Natalia Hoar; Gergonius Fallo; I Gede Arya Wiguna (Quagga: Jurnal Pendidikan dan Biologi, 2024)
Mushrooms are eukaryotic organisms with spores, without chlorophyll that reproduce sexually and asexually, mushrooms can be used by humans as food ingredients and ingredients for traditional and modern medicine. The purpose of this study was to determine the type and habitat characteristic of macroscopic fungi conducted in the kateri procted forest area Malaka Regency. Using exploration and  identification methods where the plant identification process is a process of matching a plant according to a particular taxonomi  on each research transect line. There are 28 species of macroscopic fungi namely Dacrymyces stilatus, Auricularia auricula-judae, Xylaria hypoxylon, Daldinia concentrica, Microporus xanthopus, Earliella scabrosa, Pycnoporus sanguineus, Polyporus alveolaris, Lentinus squarrosulus, Hexagonia tenuis, Trametes pubescens, Tyromyces chioneus, Marasmius oreades, Marasmius haematocephalus, Baespora myosura, Marasmius rotula, Marasmius andorsaceus, Trogia infundibiliformis, Leucocoprinus brebissonii, Lepiota helveola. Agaricus micromegathus, Bolbitius vitelinus, Mycena albicocapilaris, Crepidotus variabilis, Parasola plicatilis, Coprinopsis fragilisimus, Lycoperdon pyriforme, Pleurotus djamor. Divided into 5 Orders namely Dacrymycetales, Auriculariales, Xylariales, Polyporales, Agaricales. And 12 family namely Dacrymycetaceae, Auriculariaceae, Xylariaceae, Polyporaceae, Marasmiaceae, Agaricaceae, Bolbitiaceae, Mycenaceae, Crepidotaceae, Psathyrellaceae, Schizophyllaceae, Pleurotaceae. The most abundant habitat Characteristics were on rotten wood branches as many 9 species, on dead  wood stem many as 8 species, in leaf little many as 4 species and in soil with hums many as 7 species.